2011
DOI: 10.1016/j.jcws.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Silver Toxicity With the Use of Silver-Impregnated Dressing and Wound Vacuum-Assisted Closure in an Immunocompromised Patient

Abstract: Silver-containing topical agents are used to help prevent infectious complications in wound therapy. Toxicity from topical silver agent exposure was initially reported in 1975 and was clinically characterized by granulocytopenia. Currently, the data regarding potential toxicity associated with silver-impregnated devices are limited. A 23-year-old patient receiving chemotherapy for acute lymphoblastic leukemia presented with necrotizing fasciitis of the abdominal wall and scrotum from a Crohn disease-related ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The high content of glycerol in Ia could have increased SSD penetration in our experiments. Several studies have already shown that silver (as Ag 0 or Ag + ) can penetrate through damaged skin and reach circulation in vivo [22][23][24] or ex vivo 25 . In addition, Larese et al observed the detectable penetration of silver from AgNP applied on intact ex vivo human skin 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The high content of glycerol in Ia could have increased SSD penetration in our experiments. Several studies have already shown that silver (as Ag 0 or Ag + ) can penetrate through damaged skin and reach circulation in vivo [22][23][24] or ex vivo 25 . In addition, Larese et al observed the detectable penetration of silver from AgNP applied on intact ex vivo human skin 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have indicated that intravenous options, such as imipenem, gentamicin, vancomycin, teicoplanin, rifampicin, or lenozoid can be effective [ 19 , 21 ]. Silver nanoparticles and many other hard metals, such as zinc, copper, and arsenic also contain antimicrobial properties, but must be carefully monitored for the development of a metal toxicity [ 22 , 23 ]. Revascularization can be made possible through angioplasty, thrombolysis, and most commonly, bypass surgery [ 6 ].…”
Section: Current Treatment and Challengesmentioning
confidence: 99%
“…They also showed that impedance measurements inhibited the growth of bacteria, due to the deposit of Ag ions in the culture [ 110 ]. Ag is a widely acceptable antimicrobial molecule and the use of Ag in wound dressings has been demonstrated clinically [ 23 ].…”
Section: Biosensing In the Chronic Wound Environmentmentioning
confidence: 99%
“…bacteria, due to the deposit of Ag ions in the culture [99]. Ag is a widely acceptable antimicrobial molecule and the use of Ag in wound dressings has been demonstrated clinically [20]. Swisher et al designed a flexible, electronic device that non-invasively detects ulcers via impedance spectroscopy across a flexible electrode array in a rat model [100] They used inkjet printing to create gold-plated electrodes on a polyethylene naphthalene substrate where they used a LCR meter to detect the impedance between two locations on the array.…”
Section: Impedancementioning
confidence: 99%